The Relation of Miasms in Homoeopathic Treatment, as add on, in Management of Rheumatoid Arthritis (Advancements in Homeopathic Research, 2020)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease of unknown etiology marked by a symmetric, peripheral polyarthritis. The proposed study aims to compare the role of Homoeopathic medicines and Placebo, along with physiotherapy in management of rheumatoid arthritis. Objective: To assess pre and post NPRS for pain management in both treatment groups of rheumatoid arthritis patients and to study the relation of miasms in rheumatoid arthritis. StudyDesign: Aprospective, single blind, randomized, placebo-controlled trial. Materials and Methodology: 60 Cases of RA were randomly allocated to the two treatment groups, Homeopathic medicine group- Group A (n=30) and Placebo group- Group B (n=30) treated with individualized Homoeopathic medicine and Placebo.The outcome measures were lowering of NPRS Score in both groups after three months of treatment. Results: Among 60 cases of RA the relation of miasm with response to treatment in Group A has shown that the predominant sycoticmiasm (n=17) showed marked improvement in 7 cases with reduction in average NPRS from 7 to 2.5.The second predominant miasm found in this study is Psora- sycosis (n=7) showed marked improvement in 3 cases with reduction in average NPRS from 7 to 3.4 and in Psora (n=2) showed marked improvement in 1 case with reduction in average NPRS from 8 to 2.5.Whereas in Group B the predominant miasms Sycosis (n=14), Psora-Sycosis (n=10) and Psora (n=5) showed mild improvement in 1 case each with no specific variation in before and after average NPRS Score.The most frequently prescribed medicine was Bryonia (n=4), Rhustox (n=4), Calcareaphos (n=3), Nuxvom (n=3), Phosphorus (n=3), Calcarea carb (n=2), Chamomilla (n=2), Lycopodium (n=2), Belladonna (n=1), Benzoic acid (n=1), Berberis vul (n=1), Cinchona officinalis (n=1), Lachesis (n=1), Pulsatilla (n=1) and Silicea (n=1). Conclusion:Homeopathic medicines are effective as add on treatment in decreasing pain in cases of RA as compared to Placebo assessed by NPRS score.
Keywords: Rheumatoid Arthritis; Placebo; Homeopathy; NPRS